Transcriptome Analysis of Resistance to Fusarium Wilt in Mung Bean (Vigna radiata L.) - Chang, Yujie; Sun, Feifei; Sun, Suli; Wang, Lanfen; Wu, Jing; Zhu, Zhendong (Frontiers in Plant Science, 2021)
Fusarium wilt is a destructive soil-borne disease that threatens the production of mung bean. Mung bean lines Zheng8-4 and Zheng8-20 show high resistance and high susceptibility to Fusarium wilt, respectively. Transcriptome analysis was carried out to identify candidate genes involved in Fusarium wilt resistance using Zheng8-4 and Zheng8-20 at 0, 0.5, 1, 2 and 4 days post inoculation (dpi). Differential expression analysis showed that 3,254 genes responded to pathogen infection and were differentially expressed in the resistant and susceptible lines. Weighted gene coexpression network analysis (WGCNA) was also performed to identify five modules highly correlated with Fusarium wilt resistance, in which 453 differentially expressed genes (DEGs) were considered likely to be involved in Fusarium wilt resistance. Among these DEGs, we found 24 genes encoding resistance (R) proteins, 22 encoding protein kinases, 20 belonging to transcription factor families, 34 encoding proteins with oxidoreductase activity, 17 involved in stimulation/stress responses, and 54 annotated to pathogen resistance-related pathways. Finally, 27 annotated genes were further selected as candidate genes of Fusarium wilt resistance in mung bean. This study identifies novel potential resistance-related genes against Fusarium wilt and provides a theoretical basis for further investigation of Fusarium wilt resistance in mung bean breeding.